Review: Burden on Family Caregivers Caring for Patients with Schizophrenia and Its Related Factors - Rafiyah, Imas (Department of Nursing, Faculty of Medicine, Diponegoro University, 2011)
Background: Family caregiver is the most important person who cares for patient with schizophrenia. However when care is provided for long time, he/she may experiences the burden.Purpose: The purpose was to review concept and factors related to burden on family caregivers caring for patients with schizophrenia.Method: A literatures were searched from databases: Pubmed, CINAHL, and Science Direct. Key words used to retrieve literature include caregiver burden and schizophrenia. Searching was limited in English language, full text, and the year of publication from 2000 to 2009 was used.Results: Twenty two studies were reviewed in this paper. The result showed that the caregivers caring for patients with schizophrenia experience burden. Burden was defined as a negative impact of caring for the impaired person experienced by caregiver on their activity (objective burden) or feeling (subjective burden) that involves emotional, physical health, social life, and financial status. Factors related to burden on family caregiver were grouped into: 1) caregiver‟s factors included age, gender, educational level, income, health status, and spent time per day, knowledge of schizophrenia, culture, and coping; 2) patient‟s factors included age, clinical symptoms, and disability in daily life; 3) environmental factors included mental health service and social support.Conclusion: Definition of burden have quite same meaning and mostly factors focus on the patient‟s symptoms, demographic factors of caregiver, and time spent per day. Most of studies cannot be generalized due to small sample used in the study and that too conducted in western countries. For further research, the correlation between burden and resources of family caregiver should be investigated particularly in eastern country.Key words: burden on family caregiver, caring, schizophrenia.